Antifungal Potential of the Skin Microbiota of Hibernating Big Brown Bats (Eptesicus fuscus) Infected With the Causal Agent of White-Nose Syndrome - Lemieux-Labonté, Virginie; Dorville, Nicole A. S.-Y.; Willis, Craig K. R.; Lapointe, François-Joseph (Frontiers in Microbiology, 2020)
Little is known about skin microbiota in the context of the disease white-nose syndrome (WNS), caused by the fungus Pseudogymnoascus destructans (Pd), that has caused enormous declines of hibernating North American bats over the past decade. Interestingly, some hibernating species, such as the big brown bat (Eptesicus fuscus), appear resistant to the disease and their skin microbiota could play a role. However, a comprehensive analysis of the skin microbiota of E. fuscus in the context of Pd has not been done. In January 2017, we captured hibernating E. fuscus, sampled their skin microbiota, and inoculated them with Pd or sham inoculum. We allowed the bats to hibernate in the lab under controlled conditions for 11 weeks and then sampled their skin microbiota to test the following hypotheses: 1) Pd infection would not disrupt the skin microbiota of Pd-resistant E. fuscus; and 2) microbial taxa with antifungal properties would be abundant both before and after inoculation with Pd. Using high-throughput 16S rRNA gene sequencing, we discovered that beta diversity of Pd-inoculated bats changed more over time than that of sham-inoculated bats. Still, the most abundant taxa in the community were stable throughout the experiment. Among the most abundant taxa, Pseudomonas and Rhodococcus are known for antifungal potential against Pd and other fungi. Thus, in contrast to hypothesis 1, Pd infection destabilized the skin microbiota but consistent with hypothesis 2, bacteria with known antifungal properties remained abundant and stable on the skin. This study is the first to provide a comprehensive survey of skin microbiota of E. fuscus, demonstrating potential associations between the bat skin microbiota and resistance to the Pd infection and WNS. These results set the stage for future studies to characterize microbiota gene expression, better understand mechanisms of resistance to WNS, and help develop conservation strategies.